Can indeterminacy explain the short-run non-neutrality of money? - Fiorella De Fiore (European Central Bank (ECB), 2000)
This paper analyzes the possibility to generate indeterminacy and equilibria with short-run non-neutrality of money in a model with flexible prices, constant returns to scale in production and constant money growth rules. The model recovers previous results in the literature as particular cases. It is shown that real effects of monetary shocks, as observed in the data, can arise in four regions of the parameter space. Two regions are characterized by unreasonable assumptions, which lead to inferiority of consumption or leisure. Two regions are characterized by reasonable assumptions and by normality of the goods. However, real effects of monetary shocks require implausible parameter values.
Keywords: E13; E40; E52; 330